The Creation of Moral Education in Junior High Schools - Sugeng Priyanto, Agustinus; Sumadi, Tjipto; Rudi Casmana, Asep (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to examine the implementation of moral education at the junior high school level in Indonesia. In particular, this research focus on the conception of moral education learning and the construction of education in developing student morals. It also measures the application of moral education conducted by teachers and government policies. Moral education is considered to be an essential aspect of each level of school in Indonesia. This module teaches values of life that probably can be applied in the day-to-day living environment. The qualitative approach is utilized in this research, then documentation, interviews, and observation of schools were undertaken. The results of the study showed that moral education that was taught in secondary schools follows the policies outlined by the Government. Besides, the implementation of moral education was carried out by integrating into the school rules. Meanwhile, the teacher acts as the guardian of school order, designs, and constructs moral education by the school environment. Teachers also develop a variety of moral learning, as well as being an example in moral education.